RUNNING SPORT PROGRAM 50 METERS NUMBER OF LONG JUMP - Nurhayati Liputo; Ronal Biki (Jambura Journal of Sports Coaching, 2019)
The purpose of this study was to determine the effect of a 50-meter running speed training program on squat style long jump abilities. The study used an experimental method, by giving a treatment of 50 meters running speed training and programming for 18 meetings with a frequency of 3 times a week, the study design used the research design of One Group Pre Test and Post Test Desing. Data analysis technique is to use the formula t-test at a significant level ? = 0.05. The results of hypothesis testing data analysis obtained t table worth according to the testing criteria that accept H0 if t counts equal to or smaller than t table. Whereas reject H0 if t count is greater than t table. Therefore t count 4.72 is greater than t table (1,771), then the analysis results show H0 which means accept Ha or accept the research hypothesis. Thus the conclusion of the analysis is that there is the effect of a 50-meter running speed training on the squat style long jump ability.